Autoinhibitory properties of the parent but not of the N-oxide metabolite contribute to infusion rate-dependent voriconazole pharmacokinetics - Hohmann, Nicolas; Kreuter, Rebecca; Blank, Antje; Weiß, Johanna; Burhenne, Jürgen; Haefeli, Walter E.; Mikus, Gerd (British journal of clinical pharmacology, 2017)
Aims: The pharmacokinetics of voriconazole show a nonlinear dose-exposure relationship caused by inhibition of its own CYP3A-dependent metabolism. Because the magnitude of autoinhibition also depends on voriconazole concentrations, infusion rate might modulate voriconazole exposure. The impact of four different infusion rates on voriconazole pharmacokinetics was investigated. Methods: Twelve healthy participants received 100 mg voriconazole intravenous over 4 h, 400 mg over 6 h, 4 h, and 2 h in a crossover design. Oral midazolam (3 μg) was given at the end of infusion. Blood and urine samples were collected up to 48 h. Voriconazole and its N-oxide metabolite were quantified using high-performance liquid chromatography coupled to tandem mass spectrometry. Midazolam estimated metabolic clearance (eCLmet) was calculated using a limited sampling strategy. Voriconazole-N-oxide inhibition of cytochrome P450 (CYP) isoforms 2C19 and 3A4 were assessed with the P450-Glo luminescence assay. Results: Area under the concentration-time curve for 400 mg intravenous voriconazole was 16% (90% confidence interval: 12-20%) lower when administered over 6 h compared to 2 h infusion. Dose-corrected area under the concentration-time curve for 100 mg over 4 h was 34% lower compared to 400 mg over 4 h. Midazolam eCLmet was 516 ml min-1 (420-640) following 100 mg 4 h-1 voriconazole, 152 ml min-1 (139-166) for 400 mg 6 h-1, 192 ml min-1 (167-220) for 400 mg 4 h−1, and 202 ml min-1 (189-217) for 400 mg 2 h-1. Concentration giving 50% CYP inhibition of voriconazole N-oxide was 146 ± 23 μmol l-1 for CYP3A4, and 40.2 ± 4.2 μmol l-1 for CYP2C19. Conclusions: Voriconazole pharmacokinetics is modulated by infusion rate, an autoinhibitory contribution voriconazole metabolism by CYP3A and 2C19 and to a lesser extent its main N-oxide metabolite for CYP2C19. To avoid reduced exposure, the infusion rate should be 2 h.